Tfh cells induce intratumoral tertiary lymphoid structures. Issue 4 (April 2022) - Schmidleithner, Lisa; Feuerer, Markus
Abstract : Tertiary lymphoid structures (TLS) are highly organized ectopic structures found in nonlymphoid organs under chronic inflammatory conditions, including cancer. A recent study by Chaurio et al. reports that repression of Satb1 in CD4 + T cells can lead to increased Tfh cell differentiation, driving intratumoral TLS formation, resulting in reduced tumor growth in mice.